Biodegradable annuloplasty rings: evolution, characteristics and surgical technique - N. V. Shatelen; A. Kalangos (Кардіохірургія та інтервенційна кардіологія)
Annulus remodeling and stabilization with a ring have been demonstrated to be a mandatory step in mitral and tricuspid valve repair to ensure effective leaflet coaptation and improve long-term results. The need for a degradable ring stems from two areas in which biodegradable ring annuloplasty can theoretically fill a void: 1 – valve repair in infected valve tissue to avoid colonization of permanent implanted ring device and infection recurrence, 2 – valve repair in children, where traditional annuloplasty rings can’t be used due to the risk of acquired stenosis for lack of growth. Prophylactic anticoagulation following biodegradable ring annuloplasty is not necessary, provided that the patient has no other indication for it, as the intraannular position of the ring protects against any «blood-biodegradable ring» interaction.